Difficulty associated with donning medical compression stockings: results from a survey comparing two different compression stockings. (May 2013) - Benigni, Jean-Patrick; Branchoux, Sébastien; Bacle, Irène; Taieb, Charles
Aim: Although medical compression stockings (MCSs) represent the cornerstone of conservative treatment for patients with chronic venous disease, high rates of noncompliance exist. This study compared comfort levels and the difficulty associated with putting on/removing two different MCSs; a conventional degressive MCS (ankle pressure: 24–28 mmHg; calf pressure: 14–18 mmHg) and a progressive MCS (ankle pressure: 8–12 mmHg; calf pressure: 21–25 mmHg).Patients & methods: Women wearing class III MCSs in the past 3 months were recruited from across France to complete an at-home, investigator-led questionnaire, designed to evaluate their experience with putting on/taking off MCSs. Patients were randomized to two groups (group 1: controls, degressive stocking right leg, then left leg; group 2: degressive stocking right leg, then progressive stocking left leg).Results & conclusion: Patients (n = 102) in group 1 (controls) reported no differences after wearing the degressive MCS on the right leg then the left leg. By contrast, group 2 patients (n = 118) reported statistically significant improvements with the progressive MCS compared with the degressive MCS in all questionnaire parameters, including 'comfort' and 'ease of putting on/taking off' dimensions. Progressive MCSs were associated with significantly better outcomes (ease of putting on/taking off and comfort) than the conventional MCSs.